Molten Globule-Like Partially Folded State of Bacillus licheniformis α-Amylase at Low pH Induced by 1,1,1,3,3,3-Hexafluoroisopropanol - Adyani Azizah Abd Halim; Mohammed Suleiman Zaroog; Habsah Abdul Kadir; Saad Tayyab (The Scientific World Journal)
Effect of 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) on acid-denatured Bacillus licheniformis α-amylase (BLA) at pH 2.0 was investigated by far-UV CD, intrinsic fluorescence, and ANS fluorescence measurements. Addition of increasing HFIP concentrations led to an increase in the mean residue ellipticity at 222 nm (MRE222 nm) up to 1.5 M HFIP concentration beyond which it sloped off. A small increase in the intrinsic fluorescence and a marked increase in the ANS fluorescence were also observed up to 0.4 M HFIP concentration, both of which decreased thereafter. Far- and near-UV CD spectra of the HFIP-induced state observed at 0.4 M HFIP showed significant retention of the secondary structures closer to native BLA but a disordered tertiary structure. Increase in the ANS fluorescence intensity was also observed with the HFIP-induced state, suggesting exposure of the hydrophobic clusters to the solvent. Furthermore, thermal denaturation of HFIP-induced state showed a non-cooperative transition. Taken together, all these results suggested that HFIP-induced state of BLA represented a molten globule-like state at pH 2.0.